Statement of Treaties and International Agreements - United Nations Office of Legal Affairs (United Nations, 1988)
This monthly publication contains the statement of treaties and international agreements registered in accordance with Article 102 of the United Nations Charter. For each treaty or international agreement listed, the following information is given: registration or recording number, title, date of conclusion, date and method of entry into force, languages in which it was concluded, name of the authority which initiated the formality of registration, and the filing and recording date of that formality. The annex contains ratifications, accessions, supplementary agreements and other subsequent actions concerning the treaties and international agreements. This is a bilingual publication in English and French.